Proceedings of the 1994 Academy of Marketing Science (AMS) Annual Conference - Wilson, Elizabeth J.; Black, William C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1994 Academy of Marketing Science (AMS) Annual Conference held in Nashville, Tennessee. The research and presentations offered in this volume cover many aspects of marketing science including marketing strategy, consumer behavior, international marketing, marketing education, among others. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy$1 (Bs flagship journals, Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.s
Enhancing Learning in Advanced Marketing Courses -- Current Issues in Salesforce Management -- Consumer Information Processing: Display, Visual Stimuli, and Perceived Quality -- Methods and Logic of Theory Building and Assessment -- Marketing/Promoting Services: What is it the Customers Seek? -- Retail Shopping Behavior and Other Issues -- Comparative Marketing Studies -- Issues in Marketing Planning and Strategy -- Issues in Curriculum, Student Choice and Perception -- Exploring Models and Methods in Consumer Behavior -- Competitive Challenges in Global Markets -- Improving Quality and Relationships in Service Delivery -- Global Issues in Promotion Management -- Retailing Environment and Strategy -- Customer Retention in Service Industries -- Applied Research Methods -- Teaching Marketing Management Using the Theory of Competitive Rationality (Part 1) -- New Challenges in Industrial Marketing -- Methodological Issues and Advances in International Marketing -- Marketing Channels: Structural and Behavioral Dimensions -- Building Student Competencies -- The Influences of Peripheral Cues in Advertising -- Individual Differences and Consumer Attitudes and Behaviors -- Methods of Analysis of Marketing Data -- Euromarketing: Research in Progress and Present Issues -- Country-of-Origin Studies -- Product and Price Management -- Conceptual Marketing Issues and Some Applications in Europe -- Developing and Assessing Marketing Measures -- Green Marketing and Other External Influences to Marketing Strategy -- Issues in International Retailing -- NAFTA: Issues and Problems II -- Methods and Systems for Efficiency and Effectiveness in Marketing -- Perspectives in the Evaluation of Marketing Performance -- Gender, Ethics, and Advertising Effectiveness -- Nature of Services: Strategic Implications -- Marketing Channels Relationships -- Marketing Education Potpourri -- Consumer Choice Processes and Consumership -- Issues in Salesforce Motivation and Control.
Keywords: Economics; Marketing; Economics/Management Science; Marketing; Business Strategy/Leadership.; Sales/Distribution/Call Center/Customer Service